Cutaneous Changes in Neonates in the First 72 Hours of Birth: An Observational Study - Reddy, Harshita B.; Gandra, Nayantara R.; Katta, Tina P. (Current Pediatric Reviews, 2017)
Background: Variation in neonatal skin changes and clinical presentation is a frequent occurrence. We studied the pattern of cutaneous manifestations in new-borns <72 hours of birth. Method: We included all live babies delivered in our hospital; Babies were categorised according to age, birth weight and gestational age. Neonates were examined within 24 hours of birth and daily for skin lesions for 72 hours. Skin lesions were categorised into physiological, transient eruptions, due to infections, congenital anomalies and miscellaneous. Results: Of 200 new-borns, 108 (54%) were females; 180 (90%) full term babies (37-41 weeks). Non-consanguinity was noted in parents of 175 (87.5%) babies. One hundred and thirty one (65%) babies were delivered normally by vaginal route, and 69 (34.5%) by Caesarean section. 176 (88.0%) were average birth weight babies. Mean±SD lesion burden/neonate was 3.925±1.2 (n=785 lesions, 1-8 lesions/neonate). Transient skin lesions were frequent (n=451 in 198 patients, Mean±SD 2.30±0.76) followed by physiological conditions (n=284, Mean±SD 1.44±0.82). Infectious, developmental, iatrogenic and miscellaneous lesions were less frequent (mean±SD lesions 0.015±0.12, 0.0115±0.32, 0.015±0.12, and 0.035±0.18, respectively). Statistically significant (p<0.001) relationship was noted between gestational age and number of lesions; more number of full term babies had lesions, while number of lesions (>6) were more in preterm babies. All lesions occurred within 24 hours of birth except erythema toxicum neonatorum (n=124) wherein 80 were seen on day 1, and 43 on day 2. Conclusion: We confirm the variation in cutaneous lesions and their time of onset in neonates. Transient and physiological changes are more frequent and disappeared spontaneously. Number of lesions/neonate was more in premature babies.
Keywords: neonatal skin changes